Experience of Trained Female Teachers towards Inclusiveness at Secondary Level Classrooms - K.C., Dinesh (NPRC Journal of Multidisciplinary Research, 2025)
This study examines the perspectives of trained female educators on inclusive education within secondary classrooms, focusing on their approaches, challenges, and efforts to address diverse learning needs. A qualitative, phenomenological research design was employed, and data were collected through comprehensive, semi-structured interviews with an experienced female teacher from a community school in Budhanilkantha Municipality, Kathmandu, Nepal. Thematic analysis offered significant insights into how socio-economic diversity affects students' access to education and equity. The main findings reveal that teachers implement peer learning, project-based activities, counselling, and tailored support to bridge academic gaps and enhance inclusivity. Challenges encompass family-related issues, quota-based scholarships, and fostering positive social interactions. Educators advocate for collaborative learning environments to nurture mutual respect and empathy among students. The research concludes that inclusive education not only fosters equity but also enriches the learning experience by valuing diversity as a source of strength, ensuring every child feels acknowledged and empowered.